Anatomical Study of Pumpkin (Cucurbita moschata ‘Butternut’) - Ermayanti; Anastasya, Nadia (BIO-EDU: Jurnal Pendidikan Biologi, 2026)
Yellow Pumpkin (Cucurbita moschata) is a fruit and vegetable from the Cucurbitaceae family that has striking structural variations both microscopic and macroscopic. The study of the anatomical structure of the Yellow Pumpkin as a whole is still limited, so this study aims to study the anatomical structure of vegetative and generative organs in the species Cucurbita moschata. The research method is free-hand section for cross-sectional incisions of roots, stems, leaves, and paradermal leaves. Acetolysis method to obtain the morphological structure of flower pollen. This research is descriptive research. The parameters observed were in the form of organ constituent tissues, trichomes and stomata types, tracheal and fiber types, and pollen types. The results of the study showed that the root tissue was made up from the outside in, namely the epidermis, cortex, periticle, and vascular bundles (xylem and phloem). The trunk consists of trichoma-like epidermal tissue, cortex, xylem and phloem, as well as the trachea (spiral, annular and scalariform type) and libriform-type fibers. The leaf structure is composed of the epidermis above the polygonal shape and the lower form of the anticlinal sinuous, the anomocytic stomata type, the amphistomatic stomata distribution, and the leaf trichomes exist that are glandular and non-glandular. Pollen is spherical in shape, echinate-type exine, and is classified as pantoporate-type aperture. The results of this study can be used as basic data in the study of the anatomical structure of plants, especially cucurbitaceae.